STRATIGRAPHY AND PALYNOLOGY OF BURIED ORGANIC DEPOSITS FROM CAPE BRETON ISLAND, NOVA SCOTIA - Mott, R. J.; Prest, V. K. (Canadian Journal of Earth Sciences, 1967)
Pollen analysis of four non-glacial, sub-till deposits on Cape Breton Island, Nova Scotia, yielded pollen assemblages indicative of climates cooler than the present in that area. New radiocarbon dates from Hillsborough (>51 000 years), Bay St. Lawrence (>38 300), and Whycocomagh (>44 000 years) place the deposition of these deposits in pre-classical Wisconsin time. The Hillsborough and Whycocomagh deposits are considered to be time-equivalent based on pollen analysis. A lack of distinct assemblages at Bay St. Lawrence and Benacadie prohibits correlation with one another and with the Hillsborough and Whycocomagh beds. Inferences drawn from the pollen flora and the stratigraphy indicate an early Wisconsin interstadial age for these deposits rather than a Sangamon interglacial age. They are tentatively correlated with the St. Pierre interstade in Quebec.